2011
DOI: 10.12693/aphyspola.119.890
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Photovoltaic Properties of p-Si/PCBM:MEH-PPV Organic-Inorganic Hybrid Photodiode

Abstract: The photovoltaic and electronic properties of p-Si/poly [2-methoxy,5-(2-ethyl-hexyloxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In a previous work, Ahmad et al found that blending MEH-PPV with Alq 3 in chloroform leads to minor changes in the photoluminescence and favors the photodetection properties [18]. Similarly, Yakuphanoglu et al observed photovoltaic effects in blends of MEH-PPV with PCBM [19]. In our case, the blending process was carried out in toluene and the MEH-PPV:Alq 3 layers revealed dramatic changes on the photoluminescence spectrum, suitable for OLED devices.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…In a previous work, Ahmad et al found that blending MEH-PPV with Alq 3 in chloroform leads to minor changes in the photoluminescence and favors the photodetection properties [18]. Similarly, Yakuphanoglu et al observed photovoltaic effects in blends of MEH-PPV with PCBM [19]. In our case, the blending process was carried out in toluene and the MEH-PPV:Alq 3 layers revealed dramatic changes on the photoluminescence spectrum, suitable for OLED devices.…”
Section: Introductionsupporting
confidence: 57%
“…The optical setup consisted of a thermoelectrically cooled (TEC) USB-based photoluminescence spectrometer designed at QUBITeXp International Trade S.A.S. Colombia [19,20]. The setup consists of a 405 nm solid-state laser source focused on the samples with a 20× objective.…”
Section: Methodsmentioning
confidence: 99%